2012
DOI: 10.1111/j.1467-9701.2012.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Exchange Rates and Interest Rate Differentials: A Wavelet Approach

Abstract: This paper uses wavelet analysis to investigate the relationship between the spot exchange rate and interest rate differential for seven pairs of countries, with a small country, Sweden, included in each case. The key empirical results show that there tends to be a negative relationship between the spot exchange rate (domestic‐currency price of foreign currency) and nominal interest rate differential (approximately the domestic interest rate minus the foreign interest rate) at the shortest timescales, while a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…The negative relationship in the short run confirms the sticky price models. The results in both the short term and long term are consistent with (Andrieș et al, 2017; Scott Hacker et al, 2012) who found a positive relationship in the long term and a negative relationship in the short term.…”
Section: Data and Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The negative relationship in the short run confirms the sticky price models. The results in both the short term and long term are consistent with (Andrieș et al, 2017; Scott Hacker et al, 2012) who found a positive relationship in the long term and a negative relationship in the short term.…”
Section: Data and Resultssupporting
confidence: 90%
“…It can be observed that in mid‐2006 between 2 and 4 scales the arrows are right‐downward oriented, while in the same time for scales 16 to 32 the arrows are left‐upward oriented, which means that the interest rate is leading while the exchange rate is lagging. Figure 3 provides evidence for the existence of a bidirectional relationship between exchange rate and interest rate, and these results are consistent with Scott Hacker et al (2012) and Andrieș et al (2017).…”
Section: Data and Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Most of the empirical literature on the UIP hypothesis is concentrated in favour of developed economies (Chinn and Meredith, 2004, 2005; Engel, 2016; Ismailov and Rossi, 2018; Juselius and Assenmacher, 2017; Lothian, 2016; Golit et al , 2019), with relatively scanty literature in case of emerging economies (Beng and Le Ying, 2000; Sanchez, 2008; Jackman et al , 2013; Vithessonthi, 2014; Mladenović and Rašković, 2018). Further, one strand of literature has focused on examining the links between interest rates and exchange rates using wavelet transforms (Andrieș et al , 2017; Hacker et al , 2012; Hacker et al , 2014; Saiti et al , 2016) and DCC modelling (Bautista, 2003). Another strand of literature has considered the lagged relationships by implementing Granger causality models (Clarida and Gali, 1994; Cheng, 1999; Engel and West, 2005; Gumus, 2002; Si et al , 2018).…”
Section: Introductionmentioning
confidence: 99%